Hybrid light photocatalysis of aromatic wastes in a fluidized bed reactor - Akach, John Willis Juma Pesa (Vaal University of Technology, 2022)
The use of solar photocatalysis for the treatment of aromatic chemicals like phenol in wastewater has attracted significant attention due to the low cost of sunlight. However, sunlight is unreliable since its intensity fluctuates during the day. This drawback can be addressed by supplementing sunlight with artificial UV lamps when the solar intensity reduces. In this work, such a hybrid solar/UV lamp reactor, internally illuminated by the UV lamp and externally by sunlight, was designed. Phenol was used as the model pollutant and the nanophase Aeroxide P25 TiO2 was employed as the photocatalyst and fluidized by compressed air. The catalyst and bubble distribution in the reactor was analysed using computational fluid dynamics (CFD) while the Monte Carlo (MC) method was used to model the light distribution and reaction kinetics. Finally, a lamp controller was designed to specify the required UV lamp output as a function of the solar intensity. The CFD simulation using ANSYS CFX 17 showed that a fairly homogeneous distribution of the catalyst was achieved in the reactor. Consequently, accurate simulations of the light distribution could be achieved without considering the hydrodynamics. The MC models revealed that bubbles did not significantly influence light absorption at the optimum catalyst loading. This showed that air was a good medium for fluidization as it could provide good mixing and oxygen electron acceptor without negatively affecting light absorption. The forward scattering behaviour of the P25 TiO2 and the increase in light attenuation with catalyst loading was confirmed in this work. The optimum catalyst loading in the different reactor configurations was 0.15 g/L (tubular solar), 0.2 g/L (annular solar), 0.4 g/L (annular UV lamp), and 0.4 g/L (hybrid light). This resulted in experimental reaction rates of 0.337 mgL-1min-1 (tubular solar), 0.584 mgL-1min-1 (annular UV lamp), and 0.93 mgL-1min-1 (hybrid light). An analysis of the local volumetric rate of energy absorption (LVREA) and reaction rate profiles along the radial coordinate showed a non-uniformity which worsened with an increase in catalyst loading. The reaction order with respect to the volumetric rate of energy absorption (VREA) indicated that solar illumination resulted in a higher electron-hole recombination as compared to UV illumination. This, combined with the higher intensity of the UV lamp, resulted in a higher reaction rate under UV light as compared to sunlight, demonstrating that the UV lamp could be used to supplement sunlight. For a typical sunny day, a lamp controller was designed that could adjust the UV lamp output as a function of the solar intensity to maintain the reaction rate at a reference level while ensuring less energy consumption than an ON/OFF lamp controller. This work demonstrated the feasibility of hybrid solar/UV lamp photocatalysis reactor which could maintain the advantages of solar photocatalysis while mitigating its drawbacks.
Ph. D. (Department of Chemical Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Solar photocatalysis; Aromatic wastes; Fluidized bed reactor; Hybrid light; Photocatalysts; Photocatalytic reactor; Monte Carlo method; Dissertations, Academic -- South Africa.; Monte Carlo method.; Hazardous wastes -- Biodegradation.; Water -- Pollution.; Water -- Purification -- Biological treatment.